Early Marriage Readiness: An Analysis of Determinant Factors and Their Implications - Fitri, Novita Aidil; Wahyuningsih, Rany Rahma; Karlina, Ummi; Putri, Erinda Yustitia Tri; Alrefi, Alrefi; Minarsi, Minarsi; Akbari, Akbari; Emilia, Parida (Program Studi Bimbingan dan Konseling, Fakultas Ilmu Pendidikan, Universitas Negeri Medan, 2024)
This study aims to describe the implementation of career guidance in enhancing pre-employment mental readiness among orphans at the Muhammadiyah Boys’ Orphanage, Medan Branch. The research employed a qualitative descriptive approach using a case study design. Data were collected through in-depth interviews, participant observation, and document analysis involving caregivers, career mentors, and active foster participants in the program. The findings revealed that Islamic value–integrated career guidance significantly improved self-confidence, independence, and mental preparedness for work transition. Three key themes emerged: (1) implementation of Islamic character-based career programs, (2) enhancement of mental readiness and career orientation, and (3) mentoring strategies to overcome emotional and social challenges among orphans. These results highlight the importance of a holistic, spirituality-based approach in expanding both theoretical understanding and practical applications of Islamic career counseling within faith-based social institutions.